New additions to the fauna of the superfamily Tephritoidea (Diptera) of Morocco - El Harym, Younes; Korneyev, Valery (Zootaxa, 2023)
This work presents new data on six families, 23 genera and 30 species, 11 of which are new to North Africa: Campiglossa bidentis (Robineau-Devosidy, 1830), Carpomya (Goniglossum) wiedemanni (Meigen, 1826), Ceroxys hortulana (Rossi, 1790), Myennis octopunctata (Coquebert, 1798), Palloptera scutellata (Macquart, 1835), Physiphora clausa (Macquart, 1843), Platystoma lugubre (Robineau-Desvoidy, 1830), Seioptera vibrans (Linnaeus, 1758), Tephritis luteipes Merz 1992, Toxoneura muliebris (Harris, 1780), and Urophora hispanica Strobl 1906. Herina gyrans (Loew, 1864), Melieria omissa (Meigen, 1826), and Stearibia nigriceps Meigen, 1826 are recorded for the first time from Morocco. Dorycera punctulata Ackerman, El Harym & Freidberg, new species (Ulidiidae), is described based on specimens from Morocco. The following synonymy is established: Platystoma meridionale Hendel, 1913 = Platystoma idia Séguy, 1934, new synonym. One species of the genus Priscoearomyia is possibly a new species to be described in forthcoming revisions of this genus.